2006
DOI: 10.1021/ja061861w
|View full text |Cite
|
Sign up to set email alerts
|

Columnar Self-Assembled Ureido Crown Ethers:  An Example of Ion-Channel Organization in Lipid Bilayers

Abstract: The self-assembly of ureido crown-ether derivatives has been examined in homogeneous solution, in the solid state, and in planar bilayer membranes. The self-assembly is driven by head-to-tail hydrogen bonding between the urea functional groups. Dimers and higher oligomers are formed in CDCl3 solution as assessed by the change in the ureido NH chemical shift as a function of concentration. Single-crystal X-ray diffraction shows that an antiparallel association of the ureas produces columnar channels composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
146
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 167 publications
(156 citation statements)
references
References 29 publications
7
146
1
2
Order By: Relevance
“…1 A) or in solid hybrid membranes (Fig. 1B) (27)(28)(29). Our efforts involve now the noncovalent binding of hexylureidobenzo-15-crown-5 (1) and hexylureidobenzo-18-crown-6 (2) macrocyclic receptors,confined in a lipophilic mesoporous silica scaffolding matrix (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 A) or in solid hybrid membranes (Fig. 1B) (27)(28)(29). Our efforts involve now the noncovalent binding of hexylureidobenzo-15-crown-5 (1) and hexylureidobenzo-18-crown-6 (2) macrocyclic receptors,confined in a lipophilic mesoporous silica scaffolding matrix (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that in the solid state a dominant antiparallel packing of 2 via urea ribbons leads to extended stacks of crown ethers (27)(28)(29). Comparing the diffractograms generated from the single-crystal structure solution (Fig.…”
Section: Synthesis Of Mesoporous Dynamic Hybrid Materials and Membranesmentioning
confidence: 96%
See 2 more Smart Citations
“…Biological nanotubular complexes, such as the non-selective pore formed by α-hemolysin 2 , and the highly selective channels of ions 3 and water 4 , provide some of the most spectacular examples of supramolecular assemblies with extraordinary structural and functional sophistication. Taking lessons from biological assemblies, the recent integration of molecular design and synthesis with noncovalent forces such as hydrogenbonding, electrostatic, hydrophobic, π − π and ion-π interactions, along with metal-organic architectures and covalent capture of supramolecular assemblies, has made a significant inroad towards producing various synthetic channels and pores, either from organic building blocks or from cyclic peptides [5][6][7][8][9][10][11][12][13] . Many of these synthetic molecular and supramolecular structures exhibit interesting masstransporting properties.…”
mentioning
confidence: 99%